Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^6-2x^3+1=\left(x^3-1\right)^2\)
\(x^4+2x^2+1=\left(x^2+1\right)^2\)
a) x6 - 2x3 + 1
= (x3)2 - 2x3 + 1
= ( x3 - 1)2
b) x4 + 2x2 + 1
= ( x2)2 + 2x2 + 1
= ( x2 + 1)2
x4+x3+2x2+x+1=x4+x3+x2+x2+x+1=(x4+x3+x2)+(x2+x+1)
=x2(x2+x+1)+(x2+x+1)
=(x2+x+1)(x2+1)
=(x^4+2x^2+1)+(x^3+x)
=(x^2+1)^2+x(x^2+1)
(x^+1)*(x^2+1+x0
\(x^4+2x^2+1=\left(x^2+1\right)^2\) (Nhớ k cho mình với nhé!)
\(\left(1+2x\right).\left(1-2x\right)-x.\left(x+2\right).\left(x-2\right)\))
\(=1-\left(2x\right)^2-x.x^2-2^2\)
\(=1-4x^2-x^3-4\)
Ko bt có đúng ko nữa
x4 -2x2 +1 =x2.x2 - x2-x2 +1= - x2(1- x2) + (1 - x2)=(1-x2).(1-x2)=(1-x2)2
\(2x^4+3x^2-4x^2-6=x^2\left(2x^2+3\right)-2\left(2x^2+3\right)=\left(x^2-2\right)\left(2x^2+3\right)\)
\(=\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)\left(2x^2+3\right)\)
2x4 - x2 - 6
= 2x4 - 4x2 + 3x2 - 6
= ( 2x4 - 4x2 ) + ( 3x2 - 6 )
= 2x2( x2 - 2 ) + 3( x2 - 2 )
= ( x2 - 2 )( 2x2 + 3 )